Negative plate, preparation method thereof and lithium ion battery
By using active material coatings with different particle sizes and surface density on the current collector structure of the lithium-ion battery negative electrode sheet, the edge lithium-ion battery is solved during fast charging and low-temperature fast charging, and the effect of improving battery performance and reducing costs is achieved.
Patent Information
- Application Number
- CN202411849159.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-13
AI Technical Summary
Existing lithium-ion batteries face the problem of edge lithium-ion in fast charging and low-temperature fast charging, resulting in battery performance attenuation and safety risks, and it is difficult to take into account both cost and energy density while improving fast charging performance.
Using a current collector structure, by coating active materials with different particle sizes and surface density in different areas of the current collector, a specific particle size ratio and coating width ratio relationship is met to achieve good fast charging performance and edge lithium inhibition of the negative electrode sheet.
It realizes that lithium-ion batteries have good low-temperature fast charging performance without edge lithium-ion excision, while reducing production costs and taking into account the energy density of the battery.
Smart Images

Figure CN119786513A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium-ion batteries, and in particular to a negative electrode sheet and a preparation method thereof, and a lithium-ion battery. Background Art
[0002] Lithium-ion batteries, with their high energy density, long cycle life, and environmental friendliness, have been widely used in consumer electronics, electric vehicles, and other fields. With the continuous development of lithium-ion battery technology and the growing market demand, consumers are placing increasingly high demands on fast charging and low-temperature fast charging of lithium-ion batteries. Fast charging and low-temperature fast charging technologies can significantly shorten battery charging times and improve user experience, and are particularly important for applications such as electric vehicles. However, existing lithium-ion batteries still face many challenges in achieving fast charging and low-temperature fast charging.
[0003] Currently, the main methods for improving the fast-charging performance of lithium-ion batteries include using higher-performance anode materials and reducing the electrode's areal density. Using high-performance anode materials such as silicon-carbon composites and lithium titanate can increase the anode's specific capacity and rate performance, thereby improving the battery's fast-charging capabilities. Lowering the electrode's areal density—that is, reducing the coating thickness or amount of electrode active material—can shorten the lithium ion diffusion path within the electrode, reduce charge transfer resistance, and improve fast-charging performance.
[0004] However, both of these improvement methods have limitations. High-performance anode materials are typically expensive, potentially increasing battery production costs. While reducing electrode areal density can improve fast-charging performance, it sacrifices battery energy density, reducing the battery's capacity per unit volume or per unit mass. Therefore, achieving fast charging while balancing cost and energy density remains a major challenge.
[0005] In addition, even with the above-mentioned improvement methods, lithium-ion batteries may still experience edge lithium deposition under high-rate charging conditions. Lithium deposition refers to the uneven deposition of metallic lithium on the electrode surface during the charge and discharge process, forming lithium dendrites or dead lithium, which leads to battery performance degradation and safety hazards. Edge lithium deposition refers to the phenomenon that lithium deposition is more serious in the edge area of the battery electrode. There are two main reasons for edge lithium deposition: first, the current density distribution in the edge area of the electrode is uneven, and the current density at the edge is higher, resulting in preferential deposition of lithium ions at the edge; second, the edge area is in contact with the external environment of the battery, the heat dissipation rate is faster, and the temperature is lower, and the decrease in temperature will aggravate the occurrence of lithium deposition. Edge lithium deposition will lead to reduced utilization of electrode materials, reduced battery capacity and cycle life, and may cause safety problems.
[0006] Therefore, how to suppress lithium deposition at the electrode edge while ensuring the fast charging and low-temperature fast charging performance of lithium-ion batteries is a major problem that the industry urgently needs to solve. Summary of the Invention
[0007] The purpose of the present invention is to address the deficiencies of the prior art and provide a negative electrode sheet that can ensure the fast charging and low-temperature fast charging performance of lithium-ion batteries while inhibiting edge lithium deposition.
[0008] In order to achieve the above object, the present invention adopts the following technical solutions:
[0009] A negative electrode sheet, comprising:
[0010] current collector;
[0011] a first active material coating applied to a first region of the current collector;
[0012] a second active material coating layer applied to a second region of the current collector;
[0013] The particle size D50 of the first active material is α, and the particle size D50 of the second active material is β;
[0014] The width of the first active material coating is A1, and the width of one side of the second active material coating is A2;
[0015] Among them, α, β, A1 and A2 satisfy the following relationship: 4.3≤(α / β) 2 *A1 / A2≤61.3.
[0016] Preferably, the particle size α of the first active material is 8-12 μm, the particle size β of the second active material is 6.5-10.5 μm, the width A1 of the first active material coating is 6-9 cm, and the width A2 of one side of the second active material coating is 0.5-2 cm.
[0017] Preferably, the particle size α of the first active material and the particle size β of the second active material satisfy the relationship: α≥β.
[0018] Preferably, the surface density of the first active material coating is B1, and the surface density of the second active material coating is B2; B1 and B2 satisfy the relationship: 0.98≤B2 / B1≤1.01; and B1 is 6-15 mg / cm 2 , the B2 is 5-15.5 mg / cm 2 .
[0019] Preferably, the gram capacity of the negative electrode active material of the first active material coating is C1, and the gram capacity of the negative electrode active material of the second active material coating is C2, and C1 and C2 satisfy the relationship: 1≤C2 / C1≤1.03.
[0020] Preferably, the compaction density of the first active material coating is D1, the compaction density of the second active material coating is D2, and D1 and D2 satisfy the relationship: 0.98≤D2 / D1≤1.02.
[0021] Preferably, the negative electrode active material of the first active material coating is one or more substances selected from ordinary graphite, fast-charged graphite, hard carbon, soft carbon, silicon-carbon material, silicon monoxide, tin oxide, and phosphorus negative electrode material.
[0022] Preferably, the negative electrode active material of the second active material coating is one or more substances selected from the group consisting of fast-charging graphite, hard carbon, soft carbon, silicon-carbon material, and silicon monoxide.
[0023] In addition, the present invention also provides a method for preparing the negative electrode sheet, comprising the following steps:
[0024] Step S1, mixing water and a thickener to prepare a glue solution, mixing the first negative electrode active material and the conductive agent, adding the glue solution and mixing, adding water after the mixing is completed to disperse, and then adding a binder and dispersing to obtain a first active material coating slurry;
[0025] Step S2, mixing water and a thickener to prepare a glue solution, mixing the second negative electrode active material and the conductive agent, adding the glue solution and mixing, adding water after the mixing is completed to disperse, and then adding a binder and dispersing to obtain a second active material coating slurry;
[0026] Step S3: After setting the values of A1 and A2, the first active material coating slurry and the second active material coating slurry are simultaneously coated on the current collector using a zebra stripe coating method. After coating, the current collector is cut to obtain the negative electrode sheet.
[0027] In addition, the present invention also provides a lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet, and a separator spaced between the positive electrode sheet and the negative electrode sheet, wherein the negative electrode sheet is the above-mentioned negative electrode sheet.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] (1) The negative electrode sheet provided by the present invention is provided with a first active material coating in the first region of the current collector and a second active material coating in the second region of the current collector. The two different types of active material coatings can fully exert the rate performance of the negative electrode. The middle part is not easy to deposit lithium due to the low current density and small charging rate, so a low-fast charging type negative electrode material can be used. The edge needs to use a high-fast charging type negative electrode due to the high current density. The combination of the two negative electrode materials can ensure that the battery has good low-temperature fast charging performance without depositing lithium.
[0030] (2) The present invention sets the particle size D50 of the first active material, the particle size D50 of the second active material, the width of the first active material coating layer, and the width of one side of the second active material coating layer to satisfy the following relationship: 3≤(α / β) 2 *A1 / A2 ≤ 61.3. The material's particle size is related to the battery's rate capability, so the particle size must be optimized for the coating width to ensure fast-charging performance without lithium deposition. During low-temperature charging, lithium deposition at the battery edge can reach at least 1 / 10 the width of the negative electrode. Therefore, it's important to minimize costs by using as many low-speed-charging negative electrodes as possible while preventing lithium deposition. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 Schematic diagram of the structure of a negative electrode sheet according to an embodiment of the present invention.
[0032] Among them, 1-first area; 2-second area. DETAILED DESCRIPTION
[0033] To make the technical solutions and advantages of the present invention more clear, the present invention and its beneficial effects will be described in further detail below with reference to specific implementation methods and accompanying drawings, but the implementation methods of the present invention are not limited thereto.
[0034] The terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the quantity of the technical features being referred to. Thus, a feature specified as "first" or "second" may explicitly or implicitly include one or more of such features. In the description of the present invention, "plurality" means two or more, unless otherwise specifically defined.
[0035] According to a first aspect of the present application, the present application aims to provide a negative electrode sheet, the negative electrode sheet comprising:
[0036] current collector;
[0037] A first active material coating layer, applied to the first region 1 of the current collector;
[0038] A second active material coating layer, applied to the second region 2 of the current collector;
[0039] The particle size D50 of the first active material is α, and the particle size D50 of the second active material is β;
[0040] The width of the first active material coating is A1, and the width of one side of the second active material coating is A2;
[0041] Among them, α, β, A1 and A2 satisfy the following relationship: 4.3≤(α / β) 2*A1 / A2 ≤ 61.3. The active material particle size D50 is related to the material's kinetic performance. Larger particle sizes deteriorate the kinetics, meaning the rate performance. However, the particle size cannot be too small. If it is too small, the difference between the two will be significant, leading to overvoltage in the first coating layer due to excessive compaction, which can cause lithium deposition during charging.
[0042] Among them, when charging at low temperatures, lithium deposition at the edge of the battery is at least 1 / 10 of the width of the negative electrode. Therefore, it is necessary to use as many low-fast charging type negative electrodes as possible to reduce costs while ensuring that lithium deposition does not occur.
[0043] In some embodiments, the particle size α of the first active material is 8-12 μm, for example, 8 μm, 9 μm, 10 μm, 11 μm, or 12 μm.
[0044] In some embodiments, the particle size β of the second active material is 6.5-10.5 μm, for example, 6.5 μm, 7.5 μm, 8.5 μm, 9.5 μm, or 10.5 μm.
[0045] In some embodiments, the width A1 of the first active material coating layer is 6-9 cm, for example, 6 cm, 7 cm, 8 cm, or 9 cm.
[0046] In some embodiments, the width A2 of a single side of the second active material coating layer is 0.5-2 cm, for example, 0.5 cm, 1 cm, 1.5 cm, or 2 cm.
[0047] In some embodiments, the particle size α of the first active material and the particle size β of the second active material satisfy the relationship: α≥β.
[0048] In some embodiments, the surface density of the first active material coating is B1, and the surface density of the second active material coating is B2; B1 and B2 satisfy the relationship: 0.98≤B2 / B1≤1.01, for example, 0.98, 0.99, 1, 1.01; B1 is 6-15 mg / cm 2 , for example, it can be 6 mg / cm 2 , 7mg / cm 2 , 8mg / cm 2 , 9mg / cm 2 、10mg / cm 2 , 11mg / cm 2 , 12mg / cm 2 、13mg / cm 2 、14mg / cm 2 、15mg / cm 2 , B2 is 5-15.5 mg / cm 2 , for example, it can be 5mg / cm 2, 6mg / cm 2 , 7mg / cm 2 , 8mg / cm 2 , 9mg / cm 2 、10mg / cm 2 , 11mg / cm 2 , 12mg / cm 2 、13mg / cm 2 、14mg / cm 2 、15.5mg / cm 2 To prevent lithium deposition at the edges, the surface density of the second active material coating needs to be slightly higher than that of the first active material coating, but not too high, otherwise it will affect processing; if the coating surface density is too low, there will be a risk of foil leakage, causing lithium deposition at the negative electrode; if the coating is too thick, insufficient kinetics will occur, leading to lithium deposition.
[0049] In some embodiments, the gram capacity of the negative electrode active material of the first active material coating is C1, and the gram capacity of the negative electrode active material of the second active material coating is C2. C1 and C2 satisfy the relationship: 1≤C2 / C1≤1.03, and may be, for example, 1, 1.01, 1.02, or 1.03. The edges of the electrode sheet are prone to lithium deposition and thinning due to kinetic reasons. Therefore, the gram capacity of the negative electrode active material of the second active material coating needs to be at least the same as or slightly higher than that of the negative electrode active material of the first active material coating. However, the gram capacity of the negative electrode active material of the second active material coating cannot be too high, otherwise it will waste material, or the thickness of the two negative electrodes may be inconsistent due to design issues, increasing the difficulty of subsequent electrode sheet rolling.
[0050] In some embodiments, the compacted density of the first active material coating is D1, and the compacted density of the second active material coating is D2. D1 and D2 satisfy the relationship: 0.98≤D2 / D1≤1.02. For example, D1 and D2 may be 0.98, 0.99, 1.00, 1.01, or 1.02. The compacted densities of the first active material coating and the second active material coating should be as similar as possible to ensure that the two materials have the same rolled thickness during rolling, thereby reducing the difficulty of rolling.
[0051] In some embodiments, the width A1 of the first active material coating is 6-9 cm, for example, 6 cm, 7 cm, 8 cm, or 9 cm; the width A2 of one side of the second active material coating is 0.5-2 cm, for example, 0.5 cm, 1 cm, 1.5 cm, or 2 cm.
[0052] In some embodiments, the negative electrode active material of the first active material coating is one or more of ordinary graphite, fast-charged graphite, hard carbon, soft carbon, silicon-carbon material, silicon monoxide, tin oxide, and phosphorus negative electrode material.
[0053] In some embodiments, the negative electrode active material of the second active material coating layer is one or more of fast-charging graphite, hard carbon, soft carbon, silicon-carbon material, and silicon monoxide.
[0054] According to a second aspect of the present application, a method for preparing a negative electrode sheet is provided, comprising the following steps: Step S1, mixing water and a thickener to prepare a glue solution, mixing a first negative electrode active material and a conductive agent, adding the glue solution and mixing, adding water after the mixing is completed to disperse, and then adding a binder and dispersing to obtain a first active material coating slurry;
[0055] Step S2, mixing water and a thickener to prepare a glue solution, mixing the second negative electrode active material and the conductive agent, adding the glue solution and mixing, adding water after the mixing is completed to disperse, and then adding a binder and dispersing to obtain a second active material coating slurry;
[0056] Step S3: After setting the values of A1 and A2, the first active material coating slurry and the second active material coating slurry are simultaneously coated on the current collector using a zebra stripe coating method. After coating, the current collector is cut to obtain the negative electrode sheet.
[0057] According to a third aspect of the present application, the present application provides a lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet, and a separator separated between the positive electrode sheet and the negative electrode sheet, wherein the negative electrode sheet is the above-mentioned negative electrode sheet.
[0058] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector. The positive electrode active material layer includes a positive electrode active material. The positive electrode active material may include but is not limited to a chemical formula such as Li a Ni x Co y M z O 2-b N b (wherein 0.95≤a≤1.2, x>0, y≥0, z≥0, and x+y+z=1, 0≤b≤1, M is selected from a combination of one or more of Mn and Al, and N is selected from a combination of one or more of F, P, and S), the positive electrode active material may also be, but is not limited to, LiCoO2, LiNiO2, LiVO2, LiCrO2, LiMn2O4, LiCoMnO4, Li2NiMn3O8, LiNi 0.5 Mn 1.5The positive electrode active material may be a combination of one or more of O4, LiCoPO4, LiMnPO4, LiFePO4, LiNiPO4, LiCoFSO4, CuS2, FeS2, MoS2, NiS, TiS2, etc. The positive electrode active material may also be subjected to a modification treatment. Methods for modifying the positive electrode active material should be known to those skilled in the art. For example, the positive electrode active material may be modified by coating, doping, etc. The materials used for the modification treatment may include, but are not limited to, a combination of one or more of Al, B, P, Zr, Si, Ti, Ge, Sn, Mg, Ce, W, etc. The positive electrode current collector is generally a structure or part for collecting current. The positive electrode current collector may be any material suitable for use as a positive electrode current collector for lithium-ion batteries in the art. For example, the positive electrode current collector may include, but is not limited to, metal foil, and more specifically, may include, but is not limited to, aluminum foil.
[0059] The separator can be made of various materials suitable for lithium-ion battery separators in the art, for example, it can be a combination of one or more materials including but not limited to polyethylene, polypropylene, polyvinylidene fluoride, aramid, polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, polyester and natural fiber.
[0060] The lithium-ion battery also includes an electrolyte, which includes an organic solvent, an electrolyte lithium salt, and additives. The electrolyte lithium salt can be LiPF6 and / or LiBOB, as used in high-temperature electrolytes; can also be at least one of LiBF4, LiBOB, and LiPF6, as used in low-temperature electrolytes; can also be at least one of LiBF4, LiBOB, LiPF6, and LiTFSI, as used in overcharge-preventing electrolytes; or can be at least one of LiClO4, LiAsF6, LiCF3SO3, and LiN(CF3SO2)2. The organic solvent can be a cyclic carbonate, including PC and EC; a chain carbonate, including DFC, DMC, or EMC; or a carboxylic acid ester, including MF, MA, EA, and MP. Additives include, but are not limited to, at least one of a film-forming additive, a conductive additive, a flame retardant additive, an overcharge prevention additive, an additive to control the H2O and HF content in the electrolyte, an additive to improve low-temperature performance, and a multifunctional additive.
[0061] To make the technical solutions and advantages of the present invention more clear, the present invention and its beneficial effects will be described in further detail below with reference to specific implementation methods and accompanying drawings, but the implementation methods of the present invention are not limited thereto.
[0062] Example 1
[0063] Positive electrode preparation
[0064] The active material LiCoO2, the conductive agent superconducting carbon, the conductive carbon nanotubes, and the binder polyvinylidene fluoride (PVDF) are fully dispersed and evenly coated on the aluminum current collector in an N-methylpyrrolidone solvent system in a weight ratio of 97.6:0.6:0.5:1.3, and then cold-pressed and stripped to obtain the positive electrode sheet.
[0065] Negative electrode preparation
[0066] Step S1, mixing water and a thickener to prepare a glue solution, mixing a first negative electrode active material and a conductive agent, adding the glue solution and mixing, adding water after the mixing is completed to disperse, and then adding a binder and dispersing to obtain a first active material coating slurry, wherein the first negative electrode active material is graphite, the conductive agent is SP, the binder is SBR, and the thickener is CMC, and the weight ratio of graphite:SBR:CMC:SP=96:2:1:1;
[0067] Step S2, mixing water and a thickener to prepare a glue solution, mixing the second negative electrode active material and the conductive agent, and then adding the glue solution to mix, after the mixing is completed, adding water to disperse, and then adding a binder to disperse to obtain a second active material coating slurry, wherein the second negative electrode active material is fast-charged graphite, the conductive agent is SP, the binder is SBR, and the thickener is CMC, and the weight ratio of graphite:SBR:CMC:SP=96:2:1:1;
[0068] Step S3: After setting the values of A1 and A2, the first active material coating slurry and the second active material coating slurry are simultaneously coated on the current collector using a zebra stripe coating method. After coating, the current collector is cut to obtain the negative electrode sheet.
[0069] The particle size α of the first negative electrode active material is 10 μm, the particle size β of the second negative electrode active material is 8.5 μm, and the A1 of the prepared negative electrode sheet is 8 cm, A2 is 1 cm; B1 is 12.5 mg / cm 2 , B2 is 12.6 mg / cm 2 ; C1 is 350mAh / g, C2 is 353.5mAh / g; D1 is 1.5mg / cm 3 , D2 is 1.5 mg / cm 3 .
[0070] Isolation film
[0071] The PE surface is coated with a ceramic mixture as an isolation membrane.
[0072] Electrolyte preparation
[0073] Ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), and propyl propionate (PP) are mixed in a volume ratio of 1:1:4:4, and then fully dried lithium salt LiPF6 is dissolved in a mixed organic solvent at a ratio of 1 mol / L to prepare an electrolyte.
[0074] Battery preparation
[0075] The positive electrode sheet, separator, and negative electrode sheet are wound or stacked to produce a bare battery cell. Before winding or stacking, the cells are exposed to light three times to remove water, and then packaged and injected with electrolyte to produce a finished lithium-ion battery.
[0076] The preparation steps of Example 2-13 and Comparative Example 2-6 are the same as those of Example 1, and the only difference is the parameters of the negative electrode sheet. The parameters of each example and comparative example are shown in Table 1-2 below.
[0077] Table 1
[0078]
[0079]
[0080] Table 2
[0081]
[0082]
[0083] Performance test: The battery was placed at 0℃ and 25℃ for 2h and then charged and discharged. The charge rate was 0.5-5C, and the test was carried out at an interval of 0.5C, that is, charging was carried out at 0.5C, 1C, 1.5C, 2C, 2.5C, 3C, 3.5C, 4C, 4.5C, and 5C, and discharging was carried out at 1C. After 10 weeks of testing, the batteries of each group were disassembled to observe and record the lithium plating situation at the negative electrode.
[0084] The test results are shown in Table 3 below.
[0085] Table 3
[0086]
[0087]
[0088] It can be seen from the comparison of the results in Table 1 above that, compared with the negative electrode sheets in Comparative Examples 1-8, the negative electrode sheet provided by the present invention can ensure the low-temperature fast charging performance of the lithium-ion battery while preventing lithium deposition at the edge.
[0089] From the comparison of the data of Example 1 and Comparative Examples 1 and 2, it can be seen that in Comparative Example 1, although the parameters such as A1 and A2, α and β all meet the requirements, theoretically the low-temperature rate performance will be improved, but due to the small difference in the particle size of α and β, that is, the difference in the specific surface area of the A1 and A2 regions is too small, the lithium ion embedding sites of the two regions are not much different, and the lithium embedding capacity is equivalent, so the charge and discharge performance is also basically the same; no lithium deposition is observed at 1.5C at room temperature, but the rate performance improvement of the A2 region at low temperature does not achieve the expected effect, and marginal lithium deposition occurs at 1C. In Comparative Example 2, since the width of the A1 region is larger, more lithium ions are released during charging, and the width of the A2 region is smaller, the space provided is insufficient to receive more lithium ions released from the cathode corresponding to the A1 region, and the difference in particle size between α and β is more than 2 times, that is, the specific surface area difference between the A1 and A2 regions is too large, and the lithium ion embedding sites in the two regions are too different. The lithium embedding capacity of A1 is greatly reduced at the same rate. The above two factors are combined, resulting in the overall negative electrode performance improvement not achieving the expected effect, resulting in edge lithium deposition at 1.5C at room temperature and 1C at low temperature.
[0090] In Comparative Example 5, although (α / β) 2 *A1 / A2 is within the preset range, but due to the low specific capacity of the A2 area, under the same positive electrode conditions, the capacity of the negative electrode A2 area is excessive and insufficient, and the lithium ions released from the positive electrode cannot be fully embedded in the negative electrode, resulting in lithium deposition.
[0091] In Comparative Example 6, the compaction difference between the two is large. The excessive compaction of A1 leads to overpressure at the edge of A1 and reduced kinetics. At the same rate, the difficulty of lithium ion insertion in the A1 region increases, resulting in lithium deposition.
[0092] In Comparative Example 7, α<β, that is, the material particle size in region A2 is larger than that in region A1, and the specific surface area is smaller, so there are fewer sites available for lithium ion embedding than in region A1. As a result, under the same charge rate conditions, lithium ions are more easily accumulated in region A2, thereby leading to lithium precipitation.
[0093] In Comparative Example 8, the compaction difference between the two is large. The excessive compaction of A2 leads to overpressure at the edge of A2 and reduced dynamics. At the same temperature, lithium deposition occurs due to the increased difficulty of lithium ion embedding in A2. Conversely, excessive compaction of A2 leads to overpressure at the edge of A2 and lithium deposition.
[0094] Based on the disclosure and teachings of the above description, those skilled in the art will be able to make changes and modifications to the above embodiments. Therefore, the present invention is not limited to the above specific embodiments. Any obvious improvements, substitutions, or modifications made by those skilled in the art based on the present invention fall within the scope of protection of the present invention. In addition, although certain specific terms are used in this description, these terms are only for convenience of description and do not constitute any limitation to the present invention.
Claims
1. A negative electrode sheet, characterized in that: include: current collector; a first active material coating layer, applied to a first region of the current collector; a second active material coating layer, applied to a second region of the current collector; The particle size D50 of the first active material is α, and the particle size D50 of the second active material is β; The width of the first active material coating is A1, and the width of a single side of the second active material coating is A2; Among them, α, β, A1 and A2 satisfy the following relationship: 4.3≤(α / β) 2 *A1 / A2≤61.
3.
2. The negative electrode sheet according to claim 1, characterized in that: The particle size α of the first active material is 8-12 μm, the particle size β of the second active material is 6.5-10.5 μm, the width A1 of the first active material coating is 6-9 cm, and the width A2 of one side of the second active material coating is 0.5-2 cm.
3. The negative electrode sheet according to claim 1, characterized in that: The particle size α of the first active material and the particle size β of the second active material satisfy the relationship: α≥β.
4. The negative electrode sheet according to claim 1, characterized in that: The surface density of the first active material coating is B1, and the surface density of the second active material coating is B2; B1 and B2 satisfy the relationship: 0.98≤B2 / B1≤1.01; B1 is 6-15 mg / cm 2 , the B2 is 5-15.5 mg / cm 2 .
5. The negative electrode sheet according to claim 1, characterized in that: The gram capacity of the negative electrode active material of the first active material coating is C1, and the gram capacity of the negative electrode active material of the second active material coating is C2. C1 and C2 satisfy the relationship: 1≤C2 / C1≤1.
03.
6. The negative electrode sheet according to claim 1, characterized in that: The compaction density of the first active material coating is D1, the compaction density of the second active material coating is D2, and D1 and D2 satisfy the relationship: 0.98≤D2 / D1≤1.
02.
7. The negative electrode sheet according to claim 1, characterized in that: The negative electrode active material of the first active material coating is one or more substances selected from ordinary graphite, fast-charged graphite, hard carbon, soft carbon, silicon-carbon material, silicon monoxide, tin oxide, and phosphorus negative electrode material.
8. The negative electrode sheet according to claim 1, characterized in that: The negative electrode active material of the second active material coating is one or more substances selected from fast-charging graphite, hard carbon, soft carbon, silicon-carbon material, and silicon monoxide.
9. A method for preparing a negative electrode sheet according to any one of claims 1 to 8, characterized in that: The following steps are involved: Step S1, mixing water and a thickener to prepare a glue solution, mixing a first negative electrode active material and a conductive agent, adding the mixture to the glue solution, adding water to disperse the mixture, and then adding a binder to disperse the mixture to obtain a first active material coating slurry; Step S2, mixing water and a thickener to obtain a glue solution, mixing the second negative electrode active material with a conductive agent, adding the glue solution to mix, adding water to the mixture to disperse, and then adding a binder to disperse to obtain a second active material coating slurry; Step S3, after setting the values of A1 and A2, the first active material coating slurry and the second active material coating slurry are simultaneously coated on the current collector by a zebra stripe coating method, and after coating, the current collector is cut to obtain the negative electrode sheet.
10. A lithium ion battery, characterized in that: A negative electrode sheet comprising any one of claims 1 to 8.
Citation Information
Patent Citations
Negative plate and lithium ion battery containing the same
CN112310343A
Negative plate, battery cell and battery
CN113140693A
Battery cell and battery
CN113140695A
Negative plate and application thereof
CN115295753A
Negative plate and lithium ion battery
CN117012904A
Cited By
Silicon-carbon negative pole piece, preparation method thereof and battery
CN120895592A